Alpha7 nicotinic acetylcholine receptor agonist promotes retinal ganglion cell function via modulating GABAergic presynaptic activity in a chronic glaucomatous model - Xujiao Zhou (Nature Portfolio, 2017)
Abstract Alpha-7 nicotinic acetylcholine receptor (α7-nAChR) agonists can prevent glutamate-induced excitotoxicity in cultured retinal ganglion cells (RGCs). However, the neuroprotective effects and the mechanism of action of PNU-282987, an α7-nAChR agonist, in a chronic in vivo rat glaucoma model are poorly understood. We found that elevated intraocular pressure (IOP) downregulated retinal α7-nAChR expression. Electroretinography revealed that the amplitude of the photopic negative response (PhNR) decreased in parallel with the loss of RGCs caused by elevated IOP. PNU-282987 enhanced RGC viability and function and decreased terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL)-positive signals in RGCs. Patch-clamp recordings revealed differences in the baseline frequencies and decay times of the miniature GABAergic inhibitory postsynaptic currents (mIPSCs) of RGCs between control and glaucomatous retinal slices. The results of western blotting and immunostaining showed that glutamic acid decarboxylase 65/67 and GABA deficits persisted in glaucomatous retinas and that these deficits were reversed by PNU-282987. Patch-clamp recordings also showed that PNU-282987 significantly increased the frequency and amplitude of the GABAergic mIPSCs of RGCs. The protective effects of PNU-292987 were blocked by intravitreal administration of selective GABAA receptor antagonists. The modulation of GABAergic synaptic transmission by PNU-282987 causes de-excitation of ganglion cell circuits and suppresses excitotoxic processes.